2014
DOI: 10.5665/sleep.3470
|View full text |Cite
|
Sign up to set email alerts
|

Increased Mortality in Narcolepsy

Abstract: Narcolepsy was associated with approximately 1.5-fold excess mortality relative to those without narcolepsy. While the cause of this increased mortality is unknown, these findings warrant further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 31 publications
0
34
0
1
Order By: Relevance
“…Narcolepsy induces a 1.5-fold increase in the mortality rate compared with healthy individuals. 1 As a consequence, narcoleptic patients have approximately 2-fold increased rates of hospital or other medical services admissions. 2 Narcolepsy is often associated with a tetrad of symptoms, including, excessive daytime sleepiness (EDS), hypnagogic or hypnopompic hallucinations, sleep paralysis, and cataplexy.…”
mentioning
confidence: 99%
“…Narcolepsy induces a 1.5-fold increase in the mortality rate compared with healthy individuals. 1 As a consequence, narcoleptic patients have approximately 2-fold increased rates of hospital or other medical services admissions. 2 Narcolepsy is often associated with a tetrad of symptoms, including, excessive daytime sleepiness (EDS), hypnagogic or hypnopompic hallucinations, sleep paralysis, and cataplexy.…”
mentioning
confidence: 99%
“…It reduces functional ability, work productivity, quality of life, and psychosocial functioning [36][37][38], and also increases the risk of work-and drivingrelated accidents [39,40]. A study by Ohayon et al [41] has also shown that narcolepsy is associated with an approximately 1.5-fold higher rate of mortality relative to those without narcolepsy.…”
Section: Introductionmentioning
confidence: 95%
“…Since the majority of the epidemiological studies included patients with both NT1 and NT2 (55,56), there are no valid data related to the prevalence of NT2. Its challenging detection, due to lack of awareness of the condition, nonspecific criteria, and lack of pathognomonic features such as cataplexy, may result in under or overdiagnosis of the disorder (43).…”
Section: Nt2mentioning
confidence: 99%